Keefektifan Cinema Therapy untuk Meningkatkan Efikasi Diri Siswa SMK - Cholidahanum Wieddar Syahriar; Wardatul Djannah; Ulya Makhmudah (Universitas Sebelas Maret, 2022)
Abstract: This research aimed to determine the effectiveness of group guidance using cinema therapy technique to improve self-efficacy of the eleventh grade office administration student. This was a Quasi-Experimental Design with nonequivalent control group design consisting of experiment group and control group. The subjects of this research were the eleventh grade office administration students who had low self-efficacy totaling 9 persons each group Therefore, the amount of the subjects in this research were 18 persons. The data were collected using self-efficacy questionnaires. Based on the analysis using the Mann-Whitney U test, the calculated Z score was measured at -3,499 with a significance value of 0,000. The significance number of 0,000 is less than 0,05 so there is a significant difference between the results of pretest and post test in the research after the subjects was given treatment using guidance group with cinema therapy technique. The conclusion of this research was group guidance with cinema therapy technique was proven to be effective in improving students’ self-efficacy.Abstrak: Penelitian ini bertujuan untuk mengetahui keefektifan bimbingan kelompok teknik cinema therapy untuk meningkatkan efikasi diri peserta didik kelas XI Administrasi Perkantoran. Penelitian ini merupakan penelitian Quasi Experimental Design dengan rancangan Nonequivalent Control Group Design yang terdiri dari kelompok eksperimen dan kelompok kontrol. Subjek penelitian adalah peserta didik kelas XI Administrasi Perkantoran yang memiliki efikasi diri rendah berjumlah 9 orang pada masing-masing kelompok, sehingga jumlah keseluruhan subjek penelitian ini adalah 18 orang. Teknik pengumpulan data yang digunakan berupa angket efikasi diri. Berdasarkan analisis menggunakan uji Mann Whitney U diketahui nilai Zhitung sebesar -3,499 dengan nilai signifikansi sebesar 0,000. Angka signifikansi 0,000 lebih kecil dari 0,05, sehingga terdapat perbedaan yang signifikan antara hasil pretest dan hasil posttest pada subjek penelitian setelah diberikan treatment berupa bimbingan kelompok teknik cinema therapy. Simpulan dari penelitian ini adalah bimbingan kelompok teknik cinema therapy efektif untuk meningkatkan efikasi diri siswa.